Evolution of wet‐day and dry‐day frequency in the western Amazon basin: relationship with atmospheric circulation and impacts on vegetation - Espinoza, Jhan Carlo (2016)
This paper documents the spatiotemporal evolution of wet‐day and dry‐day frequency (WDF and DDF) in the western Amazon, its relationships with oceanic and atmospheric variability and possible impact on vegetation. WDF and DDF changed significantly during the 1980–2009 period (p < 0.05). An increase in WDF is observed after 1995 over the northern part of the western Amazon (Marañón basin). The average annual value of WDF changed from 22 days/yr before 1995 to 34 days after that date (+55% after 1995). In contrast, DDF increased significantly over the central and southern part of this region (Ucayali basin) after 1986. Average annual DDF was 16.2 days before 1986 and 23.8 days afterward (+47% after 1986). Interannual variability in WDF appears to be modulated by changes in Pacific SST and the Walker cell during the November–March season. This mechanism enhances convective activity over the northern part of the western Amazon. The increase in DDF is related to warming of the North Tropical Atlantic SST, which produces changes in the Hadley cell and subsidence over the central and the southern western Amazon. More intense seasonal hydrological extremes in the western Amazon therefore appear to be related to changes in WDF and DDF that occurred in 1995 and 1986, respectively. During the 2001–2009 period, an index of vegetation condition (NDVI) appears negatively correlated with DDF (r = −0.95; p < 0.0001). This suggests that vegetation in the western Amazon is mainly water limited, rather than light limited and indicates that the vegetation is highly sensitive to concentration of rainfall.